The Democratization of Global Governance through Civil Society Actors and the Challenge from Political Equality. (September 2019) - Erman, Eva
In the theoretical literature on global democracy, the influential transmission belt model depicts transnational civil society as a transmission belt between the public space and the empowered space (decision-making loci), assuming that civil society actors contribute to the democratization of global governance by transmitting peoples' preferences from the public space to the empowered space through involvement in the political decision-making. In this article, two claims are made. First, I argue that the transmission belt model fails because insofar as civil society has formalized influence in the decision-making, it is illegitimate, and insofar as it has informal influence, it is legitimate, but civil society's special status as transmitter is dissolved. Second, I argue that civil society is better understood as a transmission belt, not between the public space and the empowered space, but between the private space (lifeworld) and the public space. It is here that civil society is essential for democracy, with its unique capacity to stay attuned to concerns in the lifeworld and to communicate those in a publically accessible form.